2015
DOI: 10.1007/s10238-015-0339-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of SP110’s associated genes on fresh cavitary pulmonary tuberculosis in Han Chinese population

Abstract: SP110 is a promising anti-Mycobacterium tuberculosis (MTB) gene. To investigate the effects of SP110 and its associated genes, i.e., MYBBP1A and RELA, on pathological progression of MTB infection, an association study with 424 patients of fresh pulmonary tuberculosis (PTB) and 424 healthy controls was performed. Moreover, classification and regression tree and multifactor dimensionality reduction were employed to explore the effects of gene-gene interactions on cavitary PTB. The results indicated that both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
(23 reference statements)
0
15
1
Order By: Relevance
“…Two of the ultimately selected articles included data from 4 independent studies 1221. Therefore, 11 articles including 13 studies were included in our meta-analysis, with 9 articles written in English and 2 in Chinese 1218192021223233343536. The flowchart of article sifting is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the ultimately selected articles included data from 4 independent studies 1221. Therefore, 11 articles including 13 studies were included in our meta-analysis, with 9 articles written in English and 2 in Chinese 1218192021223233343536. The flowchart of article sifting is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies yielded inconsistent consequences. Abhimanyu, et al,12 Cai, et al,18 and Cong, et al19 identified the association of SP110 polymorphisms with TB by a case-control design while irrelevant results were found by Png, et al20, Fox, et al21, and Jiang, et al22 Thus, we performed a comprehensive review and updated meta-analysis with more SP110 polymorphisms, articles and subgroup analysis than before, and attempted to verify and offer an accurate and comprehensive understanding of the association between polymorphisms of SP110 gene and human TB susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Five milliliter peripheral blood samples were collected from participants in vacuum tubes containing 5% EDTA. Genomic DNA was isolated and stored using the genomic DNA purification kit (Tiangen Biotech, Beijing, China) according to the instructions [16,17].…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
“…A total of 2 ml anti-coagulated blood was drawn from each subject to extract genomic DNA using the previous methods (Cai et al 2013;Jiang et al 2016). The DNA was stored at −20℃ until it was used.…”
Section: Genotyping Analysismentioning
confidence: 99%